Identification and Characterization of MtoA: A Decaheme c-Type Cytochrome of the Neutrophilic Fe(II)-Oxidizing Bacterium Sideroxydans lithotrophicus ES-1 - Liu, Juan; Wang, Zheming; Belchik, Sara M.; Edwards, Marcus J.; Liu, Chongxuan; Kennedy, David W.; Merkley, Eric D.; Lipton, Mary S.; Butt, Julea N.; Richardson, David J.; Zachara, John M.; Fredrickson, James K.; et al. (Frontiers in Microbiology, 2012)
The Gram-negative bacterium Sideroxydans lithotrophicus ES-1 (ES-1) grows on FeCO3 or FeS at oxic-anoxic interfaces at circumneutral pH, and the ES-1-mediated Fe(II) oxidation occurs extracellularly. However, the molecular mechanisms underlying ES-1’s ability to oxidize Fe(II) remain unknown. Survey of the ES-1 genome for candidate genes for microbial extracellular Fe(II) oxidation revealed that it contained a three-gene cluster encoding homologues of MtrA, MtrB and CymA of Shewanella oneidensis MR-1 (MR-1) that are involved in extracellular Fe(III) reduction. Homologues of MtrA and MtrB were also involved in extracellular Fe(II) oxidation by Rhodopseudomonas palustris TIE-1. To distinguish them from those found in MR-1, the identified homologues were named MtoAB and CymAES-1. Cloned mtoA partially complemented an MR-1 mutant without MtrA with regards to ferrihydrite reduction. Characterization of purified MtoA showed that it was a decaheme c-type cytochrome and oxidized soluble Fe(II). Oxidation of Fe(II) by MtoA was pH- and Fe(II)-complexing ligand-dependent. Under conditions tested, MtoA oxidized Fe(II) from pH 7-9 with the optimal rate at pH 9. MtoA oxidized Fe(II) complexed with different ligands at different rates. The reaction rates followed the order Fe(II)Cl2 > Fe(II)-citrate > Fe(II)-NTA > Fe(II)-EDTA with the second-order rate constants ranging from 6.3 × 10-3 μM-1s-1 for oxidation of Fe(II)Cl2 to 1.0 × 10-3 μM-1s-1 for oxidation of Fe(II)-EDTA. Thermodynamic modeling shows that redox reaction rates for the different Fe(II)-complexes correlated with their respective estimated reaction-free energies. Collectively, these results demonstrate that MtoA is a functional Fe(II)-oxidizing protein and, by working in concert with MtoB and CymAES 1, may oxidize Fe(II) at the bacterial surface and transfer released electrons across the bacterial cell envelope to the quinone pool in the inner membrane during extracellular Fe(II) oxidation by ES-1.